Study on the Effect of Cu (II) and Zn (II) on the Accumulation of Pb (II) from Soil to the Biomass of Vegetable - Le Thi Thanh Tran; Le Van Luan; Tran Quang Hieu; Le Van Tan (International Journal of Agronomy)
Among soil pollutants, lead (Pb) is one of the toxic metal pollutants widely used in many industrial processes and occurs as a contaminant in environment. In this study, a field experiment was carried out to investigate the accumulation of lead from soil contaminated by this metal ion on the biomass of some vegetables, including spinach, lettuce, carrots, and potatoes. The results showed that lead was cumulative metal. Besides, the level of lead accumulation in soil of the studied vegetables decreased in the order of tubers of carrots, tubers of potato, spinach root, lettuce root, stems and leaves of spinach, stem and leaves of carrot, stems and leaves of potato, and stem and leaves of lettuce, respectively. Our investigations demonstrate the effect of copper and zinc micronutrient elements which play an important role in the growth and development of plants, on the accumulation of lead from contaminated soil of the studied vegetables. The obtained results showed that high concentration of copper and zinc in soil cause competition with lead in the process of absorption and accumulation in the plant. Specifically, copper and zinc showed the inhibition effect on the uptake and accumulation of lead by these plants.